2013
DOI: 10.1080/07929978.2014.961388
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced in vitro caulogenesis and quantitative estimation of aloin through HPLC in Aloe vera

Abstract: Aloe vera (Liliaceae) is well known for its medicinal properties. It contains flavonoids, saponins, tannins, alkaloids and other compounds which exhibit medicinal, cosmetic and pharmacological properties. There is a lack of production of aloe leaf to meet the industry demand and therefore the means to facilitate large-scale aloe cultivation schemes need to be developed. Because sexual reproduction by seeds is almost ineffective in Aloe vera due to male sterility and vegetative propagation by offshoots is only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Pandhair et al (2011) showed that total sugars, fructose, sucrose, starch and phenol content were higher in micropropagated leaf gel as compared to sucker-propagated plants. Addition of 20 mg L −1 tryptophan induced a 2.43-fold increase in aloin content in multiple shoots cultures (Sharma V. et al, 2013). …”
Section: Propagation Techniquesmentioning
confidence: 99%
“…Pandhair et al (2011) showed that total sugars, fructose, sucrose, starch and phenol content were higher in micropropagated leaf gel as compared to sucker-propagated plants. Addition of 20 mg L −1 tryptophan induced a 2.43-fold increase in aloin content in multiple shoots cultures (Sharma V. et al, 2013). …”
Section: Propagation Techniquesmentioning
confidence: 99%